2005
DOI: 10.1017/s0265021505000980
|View full text |Cite
|
Sign up to set email alerts
|

Fast track in liver transplantation

Abstract: Immediate extubation after liver transplantation is possible in a substantial percentage of cases; confidence, habit and a spirit of emulation are decisive factors in encouraging anaesthetists to extend this practice to the largest possible number of patients. A successful immediate extubation may be an important indicator of perioperative quality of care in liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 18 publications
5
93
1
2
Order By: Relevance
“…Donor organs damaged due to cooling and transportation can therefore recuperate much faster from the so-called preservation damage, a factor which contributes significantly towards the recovery of the recipient [11,22]. In this regard, Biancofiore et al reported on significantly lower mortality rates of recipients who were extubated in the operating theatre (1%) compared to recipients with primary extubation within the first 24 hours postoperatively (4%) and those with ventilation times of over 24 hours (42%) [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donor organs damaged due to cooling and transportation can therefore recuperate much faster from the so-called preservation damage, a factor which contributes significantly towards the recovery of the recipient [11,22]. In this regard, Biancofiore et al reported on significantly lower mortality rates of recipients who were extubated in the operating theatre (1%) compared to recipients with primary extubation within the first 24 hours postoperatively (4%) and those with ventilation times of over 24 hours (42%) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in numerous transplant centers the extubation time-However, in spite of all these advantages not all patients profit from the fast tracking concept. The rate of extubation in the operating theatre is currently approximately 80%, which implies that still about one fifth of all patients in intensive care unit receive artificial ventilation [5,8,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Uygun hastalarda gerçekleştirilen erken ekstübasyonun greft fonksiyonunu iyileştirdiği, YBÜ'de kalış süresini ve maliyeti azalttığı, nozokomiyal enfeksiyon oranını düşürdüğü gösterilmiştir. Erken ekstübasyon için hastaların seçiminin cerrahi süresine, transfüze edilen kan ürünlerinin miktarına, hastanın preoperatif durumuna (MELD skoru), greftin durumu ve iskemi süresine bağlı olduğu gösterilmiştir (86)(87)(88).…”
Section: Pulmoner Sorunlar Ve Solunumsal Yönetimunclassified
“…In recent years there is a gradual increase in the number of early extubated recipients approaching to approximately 70-80% (Forraz-Neto et al, 1999;Park et al, 2000;Biancofiore et al, 2005;Salizzoni et al, 2005). Postoperative positive airway pressure ventilation combined with sedation has been known to decrease surgical stress response, improve haemodynamic stability and facilitate early recovery; however leading to elevated intrathoracic pressures it causes an increase in pulmonary vascular resistance which in turn rises right ventricular afterload.…”
Section: Early-extubation (Fast-tracking)mentioning
confidence: 99%